Migration and the 2030 Agenda : making everyone count : migrants and refugees in the Sustainable Development Goals - Koch, Anne; Kuhnt, Jana (2020)
Zusammenfassung: With the 2030 Agenda for Sustainable Development and its guiding principle, “Leave no one behind”, the international community has set itself the goal of improving the living conditions of poor and marginalised groups. In many cases, these groups include refugees and migrants. However, they are hardly taken into account in the Sustainable Development Goals (SDGs), which are decisive for the implementation of the 2030 Agenda. As a result, there is a growing danger that existing disadvantages will become more permanent or more pronounced. Five years after the adoption of the SDGs, the balance sheet is sobering: Disaggregated data is necessary to be able to understand and monitor changes in the living conditions of migrant population groups, but these data are still lacking in most countries. In line with its overarching commitment to the implementation of the SDGs, the German government should work to ensure that migrants and refugees are systematically taken into account in the follow-up and review of the 2030 Agenda